2021
DOI: 10.3389/fpubh.2021.637151
|View full text |Cite
|
Sign up to set email alerts
|

Parent Perceptions of Changes in Child Physical Activity During COVID-19 Stay-At-Home Orders

Abstract: Purpose: The purpose of this study was to explore parent perceptions of changes in child physical activity during COVID-19 stay-at-home orders.Design: A cross-sectional study.Setting: The research team used social media, relevant organizations, and neighborhood groups to distribute the survey link in May and June of 2020.Subjects: A convenience sample of parents of children aged 5–12.Measures: Survey to assess parental perceptions of changes in children's physical activity before and during stay-at-home orders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…Thirty-four studies (11 cohort, 21 cross-sectional and 2 qualitative) reported changes in physical activity among apparently healthy children and adolescents from before to during the lockdown. Of these, 25 studies (8 cohort and 16 cross-sectional and 1 qualitative)3 27 39–61 observed a decline in physical activity, 8 (2 cohort, 5 cross-sectional and 1 qualitative)9 20 26 62–66 observed no change and 1 (cohort)19 reported an increase in physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-four studies (11 cohort, 21 cross-sectional and 2 qualitative) reported changes in physical activity among apparently healthy children and adolescents from before to during the lockdown. Of these, 25 studies (8 cohort and 16 cross-sectional and 1 qualitative)3 27 39–61 observed a decline in physical activity, 8 (2 cohort, 5 cross-sectional and 1 qualitative)9 20 26 62–66 observed no change and 1 (cohort)19 reported an increase in physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…The low prevalence of adolescents meeting MVPA guidelines declined even further during the COVID-19 pandemic. Potential reasons identified by prior studies that could explain decrease in adolescent MVPA during the pandemic include a lack of peer interaction and diminished adult supervision ( Eyler et al, 2021 ). Moreover, children receiving virtual or hybrid instruction during the pandemic were more likely to report a decrease in physical activity compared to their peers who were able to continue in-person school ( Verlenden et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding physical activity, several previous studies suggest a decrease during the lockdown (Eyler et al, 2021;Pietrobelli et al, 2020;Pombo et al, 2021;Xiang et al, 2020;Yomoda & Kurita, 2021). With respect to other leisure activities, own preliminary work showed that the frequency of interactive activities (handicrafts, board games) decreased from the beginning to the end of the first lockdown in spring 2020, suggesting that the duration of an exceptional situation may affect these activities negatively (Poulain et al, 2021).…”
Section: Introductionmentioning
confidence: 96%